Pengaruh Kualitas Pelayanan, Fasilitas, Persepsi Harga, dan Promosi Terhadap Kepuasan Konsumen Express Bahari Di Kabupaten Sumenep - Akhmad Edi Gunawan; Ahmad Ghufrony (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2020)
Each cafe has its own advantages in the menu or Product Difersity (product diversity) and is supported by facilities aspects to make consumers feel satisfied. This research was conducted a case study at Jelata café, Lobuk Village, Bluto District. In answeringo these problems, the type fof research used is the quantitative method with 60 respondents who were taken. It is known that by this analysis, the sampling uses non-probability sampling methods and the data collection technique is incident sampling by distributing questionnaires. Thep data analysis techniqueaused is the reliability data validity test, classical assumption test, normality test and linearity test and heteroscedasticity test. From the research results, it shows the results of hypothesis testing that the significant value is (X1) 0.000 <0.05 and (X2) 0.016 <0.05. This means that H1 is acceptedsand H0 is rejected, so itais said that there is a significantoinfluence on the dependentavariable so that it can besconcluded that Product Difference (X1) and wifi facilities (X2) have a partial effect on (Y) Jelata cafe consumer satisfaction.